The Philosophy Behind the Names ‘La Ode’ and ‘Wa Ode’ in the Construction of Social Identity Among the Buton People: A Systematic Literature Review - Muh. Arifin; Zulfikar Putra; Ridwan Umpi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the philosophy behind the names “La Ode” and “Wa Ode” in the construction of social identity among the Buton people through a systematic literature review (SLR) approach. Naming in traditional societies serves not only as a personal identity but also as a social symbol representing social stratification, genealogical legitimacy, and collective cultural values. The research method employs the SLR approach in accordance with the PRISMA guidelines, through the selection and analysis of 18 scientific articles indexed in Google Scholar, DOAJ, and Scopus. The results indicate that the names “La Ode” and “Wa Ode” function as mechanisms for constructing social identity based on ascribed status, which is genealogically inherited within the Buton Sultanate system. Furthermore, the symbolic meaning of these names is dynamic and undergoes transformation in the context of modernization, while still maintaining cultural legitimacy. This study also identified a gap in the literature regarding the scarcity of studies that comprehensively integrate naming philosophy with social identity theory within the SLR approach. The contribution of this study lies in the development of a conceptual model that integrates social identity theory and social construction to understand traditional naming practices as a complex and adaptive symbolic system. The conclusion is that the naming philosophy behind “La Ode” and “Wa Ode” constitutes a multidimensional social identity construction, encompassing historical, structural, and symbolic aspects